Insurance against risk? Cost and compensation of job loss in different welfare states - Beduk, Selcük; Fasang, Anette Eva; Harkness, Susan; Andrade, Stefan B.; Buyukkececi, Zafer; Helske, Satu; Karhula, Aleksi (Oxford University Press, 2026)
This study investigates the cost of job loss to household incomes, and the extent to which initial earnings losses are compensated through the labor market, within the household, and by the social security programs. Using survey and administrative data from Denmark, Finland, Germany, and the UK (1990–2018), we estimate short- and long-term effects of job loss with a dynamic difference-in-differences model. Job loss reduces household income by 17 per cent in the UK while only 5 to 6 percent in other countries during the first year. These losses gradually diminish and disappear over the long run. Across all countries, market (i.e. re-employment) is the main source of compensation, while the role of household and state compensations varies in line with the national compensation strategies. State compensation is crucial in mitigating immediate income losses, while market compensation becomes even more important over time. Household compensation mainly substitutes for weaker market and state protections.